2017
DOI: 10.1044/2017_jslhr-s-16-0248
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Intervention for Residual Rhotic Errors Via App-Delivered Biofeedback: A Case Study

Abstract: Purpose Recent research suggests that visual-acoustic biofeedback can be an effective treatment for residual speech errors, but adoption remains limited due to barriers including high cost and lack of familiarity with the technology. This case study reports results from the first participant to complete a course of visual-acoustic biofeedback using a not-for-profit iOS app, Speech Therapist's App for /r/ Treatment. Method App-based biofeedback treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Finally, the data in Lee et al (1999) are based exclusively on measures of stressed syllabic /r/ in the word bird , whereas the current speech sample represents a range of /r/ contexts, including onset /r/ as in red , /r/ in a consonant cluster as in tree , and rhotic diphthongs as in door, care, and fear . Both Flipsen et al (2001) and McAllister Byun and Tiede (2017) found significant differences in F3 and F3–F2 values in connection with different /r/ contexts. In consideration of these limitations of the normative data available, it remains unclear whether acoustic measures normalised using these data can be expected to outperform raw measures in predicting the perceptually rated accuracy of children’s rhotics.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, the data in Lee et al (1999) are based exclusively on measures of stressed syllabic /r/ in the word bird , whereas the current speech sample represents a range of /r/ contexts, including onset /r/ as in red , /r/ in a consonant cluster as in tree , and rhotic diphthongs as in door, care, and fear . Both Flipsen et al (2001) and McAllister Byun and Tiede (2017) found significant differences in F3 and F3–F2 values in connection with different /r/ contexts. In consideration of these limitations of the normative data available, it remains unclear whether acoustic measures normalised using these data can be expected to outperform raw measures in predicting the perceptually rated accuracy of children’s rhotics.…”
Section: Introductionmentioning
confidence: 91%
“…App-based acoustic biofeedback therapy is a novel way to integrate the recently demonstrated efficacy of visual-acoustic biofeedback with the increased use of apps in clinical practice. Speech Therapist’s App for /r/ Treatment (staRt) is an iOS app currently in development at New York University that uses mobile technology to generate a real-time LPC spectrum that clients can use to match an acoustic target representing correct /r/ (McAllister Byun et al, 2017). In its current iteration, the app is intended for use under the supervision of an SLP, who scores each production as correct or incorrect based primarily on auditory-perceptual judgment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the obvious growth of mHealth in home, medical, and educational settings, research supporting the outcomes of mHealth in speech-language pathology is just emerging, and research in the United States has been limited. There is a body of research that has examined the use of game-based applications for speech and language disorder intervention [16-21], as well as emerging research on apps for speech and hearing screenings [22,23] and biofeedback [24]. Numerous studies report strong child engagement and motivation with the applications, but improvement in skills and generalization of those skills is limited by methodology (ie, no control group) or is not reported [16-21,24].…”
Section: Introductionmentioning
confidence: 99%
“…There is a body of research that has examined the use of game-based applications for speech and language disorder intervention [16-21], as well as emerging research on apps for speech and hearing screenings [22,23] and biofeedback [24]. Numerous studies report strong child engagement and motivation with the applications, but improvement in skills and generalization of those skills is limited by methodology (ie, no control group) or is not reported [16-21,24]. In fact, Furlong, Morris, Erickson and Serry (2018) developed a protocol for evidence-based appraisal of mobile apps for speech sound disorders [25], and in a systematic review of the Apple iTunes store and Google Play store for apps for speech disorders they found only a small proportion of applications that would be considered very high quality or therapeutically beneficial [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation